2020
DOI: 10.3390/pr8081003
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus camaldulensis, Citrus aurantium, and Citrus sinensis Essential Oils as Antifungal Activity against Aspergillus flavus, Aspergillus niger, Aspergillus terreus, and Fusarium culmorum

Abstract: Several molds are able to colonize wood and many building products or solid wood causing losses for their valuable uses. Essential oils (EOs) from aromatic plants can be used as an ecofriendly biofungicide against the growth of several molds. EOs from Eucalyptus camaldulensis, Citrus aurantium, and C. sinensis have a broad-spectrum antimicrobial activity. EOs from of E. camaldulensis air-dried aerial parts, C. aurantium leaf and C. sinensis peel, and their combinations (1:1 v/v) were evaluated for their antifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 84 publications
(99 reference statements)
2
23
0
1
Order By: Relevance
“…Recently, some EOs have been reported to be effective in reducing decay, in quality maintenance and in the essential improvement of post-harvest life of many fruits (grape, strawberry, blueberry, raspberry, blackberry and fresh-cut fruit) [17]. In particular, aldehydes, phenols and ketones considerably inhibit pathogen growth [18][19][20][21][22]. Thymol, carvacrol and p-anisaldehyde have proven fungicidal activity and the EO rich in these components showed the highest inhibitory activity against many post-harvest pathogens, such as Botrytis spp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some EOs have been reported to be effective in reducing decay, in quality maintenance and in the essential improvement of post-harvest life of many fruits (grape, strawberry, blueberry, raspberry, blackberry and fresh-cut fruit) [17]. In particular, aldehydes, phenols and ketones considerably inhibit pathogen growth [18][19][20][21][22]. Thymol, carvacrol and p-anisaldehyde have proven fungicidal activity and the EO rich in these components showed the highest inhibitory activity against many post-harvest pathogens, such as Botrytis spp.…”
Section: Introductionmentioning
confidence: 99%
“…were found to be less susceptible to cinnamon [ 5 ]. By contrast, cinnamon methanol extract can significantly inhibit A. niger growth and also the growth in Botrytis cinerea and Fusarium moniliforme [ 15 , 19 ]. Thus, the form in which a natural compound is stabilized as a fungistatic product is important and can generate different outcomes for the inhibitory growth of the same mycelia [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the most popular products with antifungal effects are the ones that hold in their composition Chitosan, a polymer extracted from the shells of marine Crustaceans, and which has already proven its efficiency in several laboratory trials [ 14 , 15 , 16 ]. Moreover, products that contain natural extracts from the bark of the Mimosa tree, cinnamon or citrus-based have recognized antimicrobial effects [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Zeolite, a volcanic tuff whose soil improvement capacities were made known in an extensive study led by Mumpton [ 25 ], has other positive agricultural effects subsequently attested, being involved in intensification of soil microbiology and the implicit increase of soil fertility [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Citrus aurantifolia leaf essential oil showed an inhibition value against A. parasiticus (47.8%) and therefore was considered to possess the ability to suppress this fungus (Rammanee and Hongpattarakere 2011). According to a study by Abo Elgat et al (2020b), Citrus sinensis peel essential oil showed potential antifungal activity against A. flavus with a GI of 86.66% when applied at a concentration of 50 µL/mL. Dongmo et al (2009) observed that C. aurantifolia essential oil had a fungicidal inhibiting action on the radial growth of Phaeoramularia angolensis.…”
Section: Chemical Composition and The Antifungal Activity Of The Oilsmentioning
confidence: 99%
“…The peel oils of many species of Citrus showed the presence of limonene as the primary compound (Moufida and Marzouk 2003;Golmohammadi et al 2018;Okla et al 2019b;Abo Elgat et al 2020b), which provides strong antifungal activity against A. flavus (Velázquez- Nuñez et al 2013). The essential oil from C. aurantifolia showed strong inhibitory effects towards Aspergillus parasiticus and aflatoxins production (Rammanee and Hongpattarakere 2011).…”
Section: Introductionmentioning
confidence: 99%